A discrimination model for crack propagation behavior at the interface of layered composite structures considering loading rate effect. (August 2021) - Zhang, Runxu; Zhang, Xiaoyu; Kang, Jianting; Kang, Tianhe; Zhang, Bailin
Highlights: A new discriminant model was established to predict the crack propagation behavior. The accuracy of the discriminant model was verified. The sensitivity analysis of the relevant parameters was carried out. Abstract: It is difficult to accurately judge the crack propagation behavior at the interfaces of layered composite structures under impact loads. By mainly considering the influence of the loading rate on the interaction between a crack and an interface, this paper presents a new discrimination model to predict the crack propagation behavior. Based on the energy release rate criterion, which is used to judge the static crack propagation behavior at the interface of a composite structure, a discrimination model was established by introducing a general function related to the crack growth rate and combining the relationship between the loading rate and the energy release rate of the crack tip. The prediction results of the discrimination model were in good agreement with the experimental and numerical simulation results. Taking the mud–sandstone composite layer of Shihezi Formation in Linxing block as the research object, parameter sensitivity analysis was conducted using the control variable method. Parametric analysis results revealed that cracks are more likely to penetrate from high-shear-modulus, low-Poisson's-ratio, and high-density materials into low-shear-modulus, high-Poisson's-ratio, and low-density materials. A small interface inclination and large interface fracture energy are beneficial for crack penetration. In extreme layered composite structures, such as those with significant interlayer differences, large inclination angles, and small interface fracture energies, increasing the loading rate can make the deflection crack penetrate the interface.